2022
DOI: 10.1002/jgm.3449
|View full text |Cite
|
Sign up to set email alerts
|

TaqI polymorphism T/t genotypes at the vitamin D receptor gene (VDR) are associated with increased serum vitamin D levels in mild and moderate psoriasis vulgaris: A pilot study

Abstract: Background: Several types of polymorphisms in vitamin D receptor (VDR) have been found in psoriasis.Aim: this study looked at the role of the TaqI polymorphism in the VDR gene as a factor in changing plasma 25-hydroxyvitamin D (25(OH)D) levels in psoriasis patients and to see if it had any relationship with disease severity.Subjects and Methods: Clinical examination, serum (25(OH)D) levels measurement, molecular studies, TaqI genotyping by PCR and RFLP subjected for the two groups.Results: T/t genotypes of Taq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The main finding of this research is that SVD levels are much lower in psoriasis patients than in control groups. This finding matches our previous studies 13,14 . Also, Studies by Orgaz Molina et al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The main finding of this research is that SVD levels are much lower in psoriasis patients than in control groups. This finding matches our previous studies 13,14 . Also, Studies by Orgaz Molina et al.…”
Section: Discussionsupporting
confidence: 93%
“…This finding matches our previous studies. 13,14 Also, Studies by Orgaz Molina et al and Chandrasekhar et al revealed comparable findings. 22,23 Studies conducted in India, and Nepal, showed a similar outcome.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…14 In our population, several studies have been conducted to understand the relationship between genetic factors and dermatological conditions. [15][16][17][18][19][20][21][22][23][24] However, according to our knowledge, no study tries to determine the mechanisms by which miRNAs contribute to AA.…”
Section: Introductionmentioning
confidence: 99%